Hepatitis A and E Viruses in Mussels from Cherrat Estuary in Morocco: Detection by Real-Time Reverse Transcription PCR Analysis - Hanaâ Bazir; Najwa Hassou; Fatiha El Mellouli; Hasnae Zekhnini; Saliha Najib; Moulay Mustapha Ennaji (Advances in Virology)
The aim of the present study was to evaluate hepatitis A virus (HAV) and hepatitis E virus (HEV) contamination in mussels (Mytilus galloprovincialis) from Cherrat estuary (Moroccan Atlantic Coast), Morocco. In total, 52 samples (n = 12 mussels/each) were collected at four sites in the estuary, monthly, between March 2019 and March 2020. HAV and HEV were detected by real-time reverse transcription polymerase chain reaction (RT-PCR) according to the ISO/TS 15216 method. HAV was detected in 46.15% of analyzed samples. Conversely, HEV was not detected in any sample. Moreover, the HAV detection rate was significantly associated with seasonal rainfall variations. This qualitative study on HAV and HEV contamination highlights the interest of studying mussel samples from wild areas. As HAV presence in mussels represents a potential health risk, viral contamination surveillance of mussels is necessary to protect consumers. HAV shellfish contamination must be monitored at Cherrat estuary because of the role played by shellfish as HAV reservoirs and/or vehicles in fecal-oral HAV transmission.